Clinical management of an adult burned patient following alcohol intoxication: A case report - Prince Kyei Baffour; Papa Kwesi Fiifi-Yankson; Gabriel Allotey (Elsevier, 2020)
An estimated 38.1% of the world's population aged 15 years and above are regular drinkers. Alcohol consumption has been found to be one of the risk factors for morbidity, disability and mortality, accounting for 3 million deaths annually (5.3% of all deaths) globally. In Ghana, an estimated 23.3% of the population take alcohol with 2.1% being heavy drinkers.Despite efforts made in Ghana to control alcohol consumption and misuse, there have been loopholes that have allowed it to persist. This paper presents a case of a 38-year old male patient who fell face down into a tripod stove following alcohol intoxication leading to deep burns.The case is being reported to raise awareness of the dangers of alcohol consumption in relation to burns. It also seeks to generate interest and discussion on how such injuries can be prevented in future and managed if they happen to occur.It is recommended that strict measures are put in place to control the unrestricted access to alcohol and education improved to curb the numerous negative effects of alcohol consumption and misuse.